Atopy and HIV: Do basophils play a role in both? - Naimimohasses, Sara (Trinity Student Medical Journal, 2010)
Background: Recent experimental evidence has implicated a role for basophils in allergic diseases. Basophils are also believed to be stimulated in HIV-1 infection by the glycoprotein expressed on the surface of the viral envelope, gp120, and directly through viral interaction with the chemokine receptor CCR3. Objectives: To investigate absolute basophil counts and peripheral blood basophil surface marker expression in healthy individuals, patients with atopic diseases and HIV positive patients. Methods: Blood was taken from a total of 68 patients: 17 healthy adult volunteers, 18 patients diagnosed with asthma, four patients with eczema, 14 patients with a suggestive history of allergy and 15 HIV positive patients. The samples were stained with anti-CD123, anti-HLA-DR and anti-CD63 antibodies. A double gating strategy was used to isolate the basophil population and analyse CD63 expression. Results: No significant difference was found between the absolute basophil count in patients with asthma (p=0.402) and eczema (p=0.947) compared to the healthy volunteers. HIV positive patients (p=0.007) and allergic patients (p=0.022) had statistically significant lower basophil counts compared to healthy controls. No significant difference was found in the level of CD63 expression in asthma patients (p=0.521), eczema patients (p=0.288) and patients with allergies (p=0.346). HIV positive patients expressed significantly higher levels of CD63 compared to healthy volunteers (p=0.005). Conclusion: There was a significant reduction in absolute basophil counts in patients with HIV, which may be due to the virus directly infecting basophils, reducing their T1/2 in circulation. The reduction in basophil count seen in allergic patients could be explained by allergen-induced migration. Basophils from HIV positive individuals expressed significantly higher levels of CD63, possibly owing to the allergen-like function of HIV gp120. There was no evidence to suggest patients with atopic diseases expressed higher levels of CD63.